Splenic artery transposition for reconstruction of a large hepatic artery aneurysm: A case report and literature review. (June 2022) - Kumano, Koichiro; Hashimoto, Shinji; Shimomura, Osamu; Miyazaki, Yoshihiro; Doi, Manami; Takahashi, Kazuhiro; Oda, Tatsuya
Abstract: Introduction and importance: Hepatic artery aneurysms (HAAs) are rare. Typical treatment options for HAAs are surgical resection and endovascular treatment but treatment choices remain controversial. Case presentation: A 65-year-old woman was rushed to our hospital suspected to have hemorrhage. Contrast-enhanced CT showed a large 12 cm aneurysm of the common hepatic artery (CHA). We diagnosed duodenal hemorrhage due to imminent rupture of the HAA. Angiography was first performed. The inferior pancreaticoduodenal artery was embolized with a coil under interventional radiology technique for arterial bleeding control. Next, we performed resection of the aneurysm and total pancreatectomy with splenic artery reservation. We reconstructed via splenic artery transposition because of the reconstruction distance, vascular system, and stability of the anastomosis. The patient was discharged from the hospital on postoperative day 21 without any complications. Clinical discussion: There are two key points in this report. Firstly, the choice of splenic artery transposition is optimal for caliber difference and reconstruction distance. The choice of splenic artery should be considered a reliable option. Secondly, total pancreatectomy avoids exposure to pancreatic juice at the anastomosis site due to pancreatic fistula. Conclusion: Splenic artery transposition for HAA is advantageous in adjustability of the caliber difference and securing of sufficient distance. In addition, total pancreatectomy may be acceptable in patients with a normal pancreas to avoid fatal complications such as disruption of the anastomosis and reconstructed artery due to pancreatic juice exposure. Highlights: Visceral artery aneurysms are rare and often involve the hepatic and splenic arteries. Typical treatment for HAAs are surgical resection and endovascular treatment but treatment choices remain controversial. The reconstruction via splenic artery transposition is an option for reconstruction after resection of HAAs. Splenic artery transposition is advantageous in adjustability of the caliber difference, securing of sufficient distance.